Waste mineral oil suspension bed hydrogenation catalysis treatment process

By using a multi-stage countercurrent extraction-adsorption coupling process with tungsten and copper active components loaded on a modified alumina-titanium oxide composite carrier, the problem of deep removal of organochlorine and organosilicon from waste mineral oil was solved, enabling long-term operation of the catalyst and improvement of product oil quality.

CN121109056AActive Publication Date: 2025-12-12HUBEI ANNAIJI ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202511657137.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2025-12-12
Estimated Expiration
2045-11-13

AI Technical Summary

Technical Problem

Existing technologies are ineffective at removing organochlorine and organosilicon impurities from waste mineral oil, leading to catalyst poisoning and equipment corrosion. Furthermore, traditional methods are inefficient, adsorbents are prone to saturation and failure, and are difficult to operate for long periods.

Method used

Tungsten and copper active components were loaded onto a modified alumina-titanium oxide composite carrier. Through a multi-stage countercurrent extraction-adsorption coupling process, selective hydrogenation and dechlorination and chemical fixation were performed using WS2 and CuS active phases, followed by organosilicon alcoholysis and countercurrent extraction with methanol solvent to achieve deep removal.

Benefits of technology

It significantly extends the operating cycle of the hydrogenation catalyst, improves the quality of the product oil, avoids catalyst poisoning and equipment corrosion, and improves mass transfer efficiency and adsorbent lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121109056A_ABST
    Figure CN121109056A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of regeneration treatment of waste mineral oil, and particularly relates to a hydrogenation catalysis treatment process for a waste mineral oil suspension bed. The method aims at the problem of deep removal of impurities such as organic chlorine and organic silicon in waste mineral oil. A novel multifunctional composite adsorbent is prepared, a modified aluminum oxide-titanium oxide composite carrier is used as a basis, a main active metal tungsten and an auxiliary agent metal copper are loaded, and the main active metal tungsten and the auxiliary agent metal copper are converted into corresponding sulfides through vulcanization treatment; through multi-stage countercurrent contact, impurities such as chlorine and silicon in the waste oil are deeply removed, the process can efficiently remove organic chlorine and silicon impurities in the waste mineral oil, the service life of a hydrogenation catalyst is remarkably prolonged, the product quality is improved, and downstream equipment is prevented from being corroded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste mineral oil regeneration and treatment, specifically relating to a catalytic treatment process for waste mineral oil suspension bed hydrogenation. Background Technology

[0002] Waste mineral oil, due to long-term use, becomes contaminated with various impurities, including degradation products of lubricating additives, abrasive metal particles, and foreign contaminants. Among these, the presence of organochlorine and organosilicon impurities poses a particularly significant threat to regeneration: chlorine compounds can form hydrogen chloride during subsequent distillation and hydrogenation processes, causing equipment corrosion and poisoning / deactivation of the hydrogenation catalyst. Silicon impurities readily decompose and deposit as silica during hydrogenation, blocking catalyst pores and active sites. Therefore, achieving deep removal of organochlorine and silicon from waste mineral oil is a key challenge to ensuring the long-term operation of the regeneration process and product quality.

[0003] Current methods for treating chlorine and silicon impurities in waste mineral oil remain incomplete. Traditionally, a combination of physical and chemical treatments is used, such as distillation combined with bleaching earth adsorption, or distillation combined with solvent refining. However, conventional adsorbents like bleaching earth primarily remove polar impurities such as colloids and oxides, with limited removal rates for organochlorines and organosilicones. Furthermore, adsorbents are prone to saturation and failure, requiring frequent replacement. Alternatively, solvent extraction pretreatment before hydrogenation can be employed, such as washing the waste oil with polar solvents like methanol. However, simple solvent extraction is not effective against silicon impurities, and high-chlorine waste oil often requires multi-stage extraction to barely meet standards. In addition, directly using fixed-bed catalytic hydrogenation for dechlorination / desiliconization also presents problems. Conventional supported dechlorination catalysts are easily deactivated by chlorine poisoning in high-chlorine waste oil, making long-term operation difficult. Simultaneously, waste oil often contains a certain amount of unsaturated olefins; if direct fixed-bed hydrogenation is used, olefins are prone to polymerization and coking, leading to bed blockage.

[0004] In summary, existing technologies are insufficient to simultaneously and efficiently address the deep removal of organochlorines and silicon from waste mineral oils. There is an urgent need for an improved processing technology to protect subsequent hydrogenation catalysts and improve the quality of recycled oil. Summary of the Invention

[0005] This invention provides a suspended bed hydrocatalytic treatment process for waste mineral oil, aiming to solve the problem of deep removal of impurities such as organochlorine and organosilicon from waste mineral oil. It proposes a comprehensive solution combining novel composite adsorbents and multi-stage countercurrent extraction-adsorption coupling. This treatment maximizes the removal of chlorine and silicon impurities before the hydrogenation reaction, preventing catalyst poisoning and equipment corrosion. Simultaneously, it also removes harmful components such as colloids and metals from the waste oil, thereby significantly extending the operating cycle of the hydrogenation unit and improving the quality of the product oil.

[0006] The specific technical solution is as follows: A waste mineral oil suspension bed hydrocatalytic treatment process is as follows: S1: Preparation of composite carrier.

[0007] S11: Dissolve aluminum nitrate in deionized water and tetrabutyl titanate in anhydrous ethanol, then mix the two under stirring to form a salt solution mixture.

[0008] S12: The salt solution mixture prepared in S11 is added dropwise in parallel with the precipitant ammonia. After the addition is complete, the mixture is stirred, aged, washed, and dried to obtain a dry powder.

[0009] S13: The dried powder prepared in S12 is mixed with the adhesive solvent dilute nitric acid, the extrusion aid guar gum powder, and the lubricant graphite. The mixture is then extruded into strips using an extruder and finally calcined to obtain the modified alumina-titanium oxide composite carrier.

[0010] S2: Active component loading.

[0011] S21: Dissolve ammonium metatungstate and copper acetate together in deionized water and stir to obtain an impregnation solution.

[0012] S22: The impregnation solution prepared in S21 is used to impregnate the modified alumina-titanium oxide composite carrier prepared in S13 with an equal volume, followed by aging, drying, programmed temperature sulfidation, and passivation to obtain a multifunctional composite adsorbent.

[0013] S3: Multi-stage countercurrent extraction-adsorption coupling process.

[0014] S31: Waste mineral oil is filtered and dehydrated to remove mechanical impurities, solid particles, free water, and emulsified water; then it is pressurized and mixed with hydrogen to obtain an oil-hydrogen mixture.

[0015] S32: The oil-hydrogen mixture prepared by S31 enters from the bottom of the adsorption tower, while the oxygen-containing solvent methanol is pressurized and enters from the top. The oil phase passes through a fixed bed containing a multifunctional composite adsorbent prepared by S22 to obtain purified oil.

[0016] S33: The purified oil prepared in S32 is cooled and then subjected to gas-liquid separation under high pressure. The liquid phase is depressurized to remove dissolved trace amounts of solvent and light hydrocarbons, resulting in the final purified oil product.

[0017] Furthermore, the parameters for the co-current dripping described in S12 are: temperature 60–80°C, pH 9.

[0018] The washing described in S12 involves washing with deionized water at 60–80°C until no chloride ions are precipitated in the filtrate when tested with silver nitrate solution.

[0019] The drying process described in S12 has the following parameters: temperature 120℃, duration 12h.

[0020] The roasting parameters described in S13 are as follows: heating rate 3℃ / min, temperature 500~600℃, and holding time 4~6h.

[0021] The modified alumina-titanium oxide composite carrier described in S13 contains a polymer solvent of dilute nitric acid with a mass ratio of 2-6 wt%, an extrusion aid of guar gum powder with a mass ratio of 2-5 wt%, and a lubricant of graphite with a mass ratio of 1-3 wt%.

[0022] Furthermore, the drying process described in S22 has the following parameters: temperature 100-120°C, duration 6-8 hours.

[0023] The programmed temperature rise vulcanization described in S22 has the following parameter settings: first, an inert gas is introduced to purge air, and then a sulfur-containing atmosphere is introduced; in the low-temperature stage, the temperature is raised from room temperature to 150°C at a rate of 1°C / min; in the medium-temperature stage, the temperature is raised from 150°C to 250°C at a rate of 2°C / min; in the high-temperature stage, the temperature is raised from 250°C to 380°C at a rate of 1°C / min, and the holding time is 3–5 hours; the sulfur-containing atmosphere is H2 containing 10% H2S.

[0024] The passivation described in S22 is performed using an inert gas N2 containing 1% O2 at room temperature.

[0025] The multifunctional composite adsorbent described in S22 has the following composition of raw materials in the following mass percentages: 10-30% tetrabutyl titanate, 15-25% ammonium metatungstate, 3-8% copper acetate, and the balance being aluminum nitrate.

[0026] Furthermore, the pressure boost described in S31 has the following parameter settings: pressure is 4.0 MPa.

[0027] The hydrogen gas described in S31 has a volume ratio of 300:1 to 500:1 with the waste lubricating oil.

[0028] The oxygen-containing solvent methanol described in S32 has a mass ratio of 0.08:1 to 0.15:1 with the oil-hydrogen mixture.

[0029] The high pressure described in S33 has the following parameter settings: pressure 4.0 MPa, temperature 50℃.

[0030] The pressure reduction described in S33 has the following parameter settings: first-stage pressure reduction: 0.8-1.2 MPa, second-stage pressure reduction: 0.3-0.5 MPa, and third-stage pressure reduction: 0.05-0.15 MPa.

[0031] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention achieves deep removal of chlorine and silicon impurities through the synergistic effect of chemical adsorption and catalytic reaction of the adsorbent and extraction and alcoholysis of the solvent.

[0032] 2. This invention improves mass transfer efficiency and reduces the amount of solvent and adsorbent used by using a countercurrent operation mode. Attached Figure Description

[0033] Figure 1 This is a flow chart of a waste mineral oil suspension bed hydrogenation catalytic treatment process.

[0034] Figure 2 This is a scanning electron microscope image of the modified alumina-titanium oxide composite support.

[0035] Figure 3 This is a comparison chart of the organochlorine removal rate and gum removal rate of the oils finally prepared in Examples 1-4 and Comparative Examples 1-3.

[0036] Figure 4 This is a comparison chart of the organosilicon removal rate and metal removal rate of the oils finally prepared in Examples 1-4 and Comparative Examples 1-3. Detailed Implementation

[0037] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.

[0038] This invention proposes a suspended bed hydrogenation catalytic treatment process for waste mineral oil. A novel multifunctional composite adsorbent is prepared, based on a modified alumina-titanium oxide composite support, loaded with the main active metal tungsten and the auxiliary agent copper, and converted into corresponding sulfides through sulfidation treatment. The waste mineral oil flows from bottom to top, while the oxygen-containing solvent flows from top to bottom in a countercurrent process, ensuring that each stage maximizes extraction and adsorption efficiency. Organochlorides in the waste mineral oil are hydrogenated to HCl and captured by the adsorbent, while organosilicones undergo alcoholysis and adsorption removal. This process extends the lifespan of the hydrogenation catalyst, improves product quality, and prevents corrosion of downstream equipment. (See attached diagram) Figure 1 The image shows a waste mineral oil suspension bed hydrocatalytic treatment process, the detailed technical solution of which is as follows: 1. Preparation of multifunctional composite adsorbents A modified alumina-titanium oxide composite support is employed. Alumina provides a high specific surface area and good mechanical strength; the introduction of titanium oxide modulates the acidity of the support, and its Lewis acid sites exhibit stronger adsorption affinity for molecules containing polar impurities such as chlorine and silicon. A unique bimodal pore size distribution: small and medium pores provide a large specific surface area, ensuring a high degree of dispersion of active centers; large pores allow large molecular organosilicon and colloid impurities to diffuse smoothly into the adsorbent interior, preventing rapid pore clogging and significantly improving adsorption capacity and efficiency.

[0039] Tungsten was chosen over the more common molybdenum because the hydrogenation activity of the WS2 phase formed after sulfidation is similar to that of MoS2, but its hydrogenolysis activity for C-Cl bonds is higher. Furthermore, the WS2 wafers have a higher stacking density, a more stable structure, and stronger resistance to poisoning. Its function is twofold: firstly, to hydrogenate and dechlorinate unstable organochlorides to generate HCl and hydrocarbons; and secondly, to hydrogenate and remove sulfur, nitrogen, and oxygen components from impurities, preventing deactivation of the adsorbent surface due to coking. Copper sulfides were chosen as the auxiliary agent because they have extremely strong chemical adsorption and fixation capabilities for chloride and silicon ions: the generated HCl immediately reacts with CuS to form stable and non-toxic CuCl2, achieving permanent chlorine fixation and preventing HCl corrosion of downstream equipment; organosilicon compounds readily decompose or alcoholyze on hydrogenation and acidic support surfaces to generate silanols, which react with Cu to form stable silicates (such as CuSiO3), thus firmly chemically fixing silicon to the adsorbent and preventing its migration and poisoning of subsequent catalysts.

[0040] A programmed temperature in-situ vulcanization process is used to directly convert the precursor into the target active phase (WS2, CuS). Compared with pre-vulcanizing agents, this method results in higher dispersion of the active phase, stronger bonding with the carrier, and higher activity.

[0041] Specifically: Aluminum nitrate was dissolved in deionized water, and tetrabutyl titanate was dissolved in anhydrous ethanol. The two solutions were then mixed under stirring to form a salt solution mixture. This salt solution mixture was added dropwise with ammonia water as a precipitant. After the addition was complete, the mixture was stirred, aged, washed, and dried to obtain a dry powder. The dry powder was mixed with dilute nitric acid (a peptizing agent), guar gum powder (an extrusion aid), and graphite (a lubricant), then extruded into strips using an extruder. Finally, the mixture was calcined to obtain a modified alumina-titanium oxide composite carrier. Ammonium metatungstate and copper acetate were dissolved together in deionized water and stirred to obtain an impregnation solution. The modified alumina-titanium oxide composite carrier was impregnated with the impregnation solution in an equal volume, followed by aging, drying, programmed temperature sulfidation, and passivation to obtain a multifunctional composite adsorbent.

[0042] Aluminum nitrate provides Al 3+ Ions, tetrabutyl titanate provides Ti 4+The use of organic titanium esters instead of inorganic titanium salts avoids the introduction of difficult-to-elute inorganic anions. Co-current dropwise addition and constant pH ensure that the supersaturation of the solution remains constant throughout the precipitation process, thereby enabling uniform nucleation and growth of Al(OH)3 and Ti(OH)4 nanoparticles, achieving a high degree of mixing of Al and Ti at the molecular level and avoiding component segregation. Aging causes the initially formed amorphous hydroxide to undergo Ostwald ripening, dissolving small particles and redepositing them on larger particles, resulting in a more complete crystal form and larger particles, which is beneficial for the subsequent formation of a more stable porous structure. Washing is to thoroughly remove Na+. + NO 3- NH 4+ Impurity ions, such as those present in the form of precipitates, remain after high-temperature calcination, damaging the acidity of the carrier or becoming ash. The role of the peptizing agent is to dissolve the oxide powder, forming a colloid, thus providing better plasticity and adhesion during extrusion. The extrusion aid burns away during calcination, leaving channels and increasing the porosity of the carrier. Calcination serves two purposes: first, it removes chemically bound water and decomposes precursors such as nitrates; second, it promotes the transformation of amorphous hydroxides into stable oxides with specific crystal phases and pore structures. At this temperature, Al(OH)3 transforms into γ-Al2O3 with a high specific surface area, and Ti(OH)4 transforms into anatase TiO2. 2; Slow, programmed heating helps to form uniform grain size and a stable bimodal pore size distribution.

[0043] Equal-volume impregnation ensures that the solution volume exactly fills all the pores of the carrier without any excess liquid water. This allows the active metal precursor to remain within the pores during drying, achieving uniform distribution through capillary action. Aging allows the metal salt solution to diffuse and redistribute further from the outer surface and larger pores of the carrier to the interior and finer pores, using capillary forces and concentration gradients. This achieves relatively uniform distribution throughout the carrier particles, preventing active sites from concentrating only on the surface. Temperature-programmed sulfidation is crucial for forming a highly dispersed active phase. The entire process involves multiple stages of physicochemical changes: a low-temperature stage to remove physically adsorbed water, a medium-temperature stage for precursor decomposition (e.g., copper acetate decomposition). such as the decomposition of ammonium metatungstate The high-temperature stage is the sulfidation reaction stage. The generated metal oxides undergo a sulfidation reaction with H2S to generate the final target active phase: such as... Passivation involves the extremely slow oxidation of the surface of active sulfide particles, forming a dense oxide protective film several molecular layers thick. This film prevents the internal active sulfide phase from coming into contact with air and continuing to oxidize or burn violently.

[0044] 2. Processing technology Countercurrent operation is the most efficient mass transfer method in chemical separation. The heavier phase flows from bottom to top, and the lighter phase from top to bottom, ensuring thorough contact between the two phases within the column. At the top, the nearly pure oil phase comes into contact with fresh solvent containing trace impurities, achieving final purification; at the bottom, the solvent saturated with impurities comes into contact with the feed oil, which has the highest impurity concentration. This creates a stable concentration gradient throughout the column, maximizing the driving force for mass transfer, thus achieving higher removal efficiency and lower solvent consumption for the same column height and adsorbent dosage.

[0045] The loaded multifunctional composite adsorbent provides a huge specific surface area and active sites, selectively adsorbing Cl and Si, and carrying out catalytic hydrogenation dechlorination and chemical fixation reactions through its active centers.

[0046] Oxygenated solvents, as extractants, can dissolve some of the more polar organochlorides and silicides in the feedstock oil. More importantly, they act as reaction promoters, especially under heating and the potential influence of acidic support surfaces, facilitating the alcoholysis of stable Si-OC bonds.

[0047] Specifically: Waste mineral oil is filtered and dehydrated to remove mechanical impurities, solid particles, free water, and emulsified water. It is then pressurized and mixed with hydrogen to obtain an oil-hydrogen mixture, which enters from the bottom of the adsorption tower. Methanol, an oxygen-containing solvent, is pressurized and enters from the top. The oil phase passes through a fixed bed containing a multifunctional composite adsorbent to obtain purified oil. After cooling, the purified oil undergoes high-pressure gas-liquid separation. The liquid phase is then depressurized to remove dissolved trace solvents and light hydrocarbons, yielding the final purified oil product.

[0048] The pressurization is to maintain all materials in the liquid phase at the operating temperature, preventing the vaporization of solvents and light components, and ensuring normal hydrodynamic and mass transfer conditions. Pre-mixing hydrogen ensures that hydrogen can be fully dissolved and dispersed in the oil phase, providing an immediate hydrogen source for the hydrodechlorination reaction in the adsorbent bed and establishing a reducing atmosphere for the entire system. The denser oil phase flows from bottom to top, while the less dense solvent phase flows from top to bottom, allowing for sufficient and efficient countercurrent contact. Oxygen-containing solvents such as methanol are polar solvents with good selective solubility for polar organochlorides and silicides in the feed oil, extracting them from the oil phase to the solvent phase. Under the catalysis of the system operating temperature and the weakly acidic sites on the adsorbent carrier surface, the solvent can promote the alcoholysis reaction of stable Si-OC bonds. Impurities in the upward-flowing oil phase are selectively adsorbed by the high specific surface area and active sites of the adsorbent bed. The WS2 center provides hydrogenation activity, hydrogenating the Cl-C bond. The generated HCl immediately reacts with CuS to form stable metal chlorides, which are then fixed. Silicides are chemically adsorbed and react to form stable silicates, which are also fixed. The downward-flowing solvent phase continuously washes the adsorbent bed, desorbing heavy impurities, colloids, and reaction intermediates physically adsorbed on the outer surface and near the pores of the adsorbent. These are then carried away with the solvent flow, alleviating pore blockage and surface coking of the adsorbent and extending its single-cycle lifespan.

[0049] Example 1

[0050] A waste mineral oil suspension bed hydrocatalytic treatment process is as follows: Table 1 Main Raw Materials

[0051] S1: Preparation of composite carrier.

[0052] S11: Dissolve aluminum nitrate in deionized water and tetrabutyl titanate in anhydrous ethanol, then mix the two under stirring to form a salt solution mixture.

[0053] S12: The salt solution mixture prepared in S11 is added dropwise in parallel with the precipitant ammonia. After the addition is complete, the mixture is stirred, aged, washed, and dried to obtain a dry powder. The parameters for the parallel-flow addition are: temperature 70℃, pH 9; and washing with 70℃ deionized water.

[0054] S13: The dried powder prepared in S12 is mixed with dilute nitric acid (a binder), guar gum powder (an extrusion aid), and graphite (a lubricant). The mixture is then extruded into strips using an extruder and finally calcined to obtain the modified alumina-titanium oxide composite carrier. The mass percentages of the binder (dilute nitric acid) are 3.5 wt%, the extrusion aid (guar gum powder) is 3 wt%, and the lubricant (graphite) is 2 wt%. The calcination parameters are: heating rate 3℃ / min, temperature 550℃, and holding time 5 h. Figure 2 The image shows a scanning electron microscope (SEM) image of the prepared modified alumina-titanium oxide composite support. The morphology of the composite support was analyzed by field emission scanning electron microscopy (FET). The accelerating voltage was 5 kV, the working distance was 7 mm, and the magnification was 12000x.

[0055] S2: Active component loading.

[0056] S21: Dissolve ammonium metatungstate and copper acetate together in deionized water and stir to obtain an impregnation solution.

[0057] S22: The impregnation solution prepared in S21 is used to impregnate the modified alumina-titanium oxide composite carrier prepared in S13 with an equal volume, followed by aging, drying, programmed temperature-increasing sulfidation, and passivation to obtain a multifunctional composite adsorbent. The drying parameters are set as follows: temperature 110℃, duration 7h; the sulfidation parameters are set as follows: first, inert gas is introduced to purge air, then a sulfur-containing atmosphere is introduced; in the low-temperature stage, the temperature is increased from room temperature to 150℃ at a rate of 1℃ / min; in the medium-temperature stage, the temperature is increased from 150℃ to 250℃ at a rate of 2℃ / min; in the high-temperature stage, the temperature is increased from 250℃ to 380℃ at a rate of 1℃ / min, and the holding time is 4h; the sulfur-containing atmosphere is H2 containing 10% H2S. The multifunctional composite adsorbent has the following composition by mass percentage: tetrabutyl titanate 20%, ammonium metatungstate 20%, copper acetate 5%, and the balance being aluminum nitrate.

[0058] S3: Multi-stage countercurrent extraction-adsorption coupling process.

[0059] S31: Waste mineral oil is filtered and dehydrated to remove mechanical impurities, solid particles, free water, and emulsified water; then it is pressurized and mixed with hydrogen gas to obtain an oil-hydrogen mixture. The volume ratio of hydrogen gas to waste lubricating oil is 400:1.

[0060] S32: The oil-hydrogen mixture prepared in S31 enters from the bottom of the adsorption tower, while the oxygen-containing solvent methanol, after pressurization, enters from the top. The oil phase passes through a fixed bed containing the multifunctional composite adsorbent prepared in S22, resulting in purified oil. The mass ratio of the oxygen-containing solvent methanol to the oil-hydrogen mixture is 0.12:1.

[0061] S33: The purified oil prepared in S32 is cooled and then subjected to high-pressure gas-liquid separation. The liquid phase is depressurized to remove dissolved trace amounts of solvent and light hydrocarbons, yielding the final purified oil product. The depressurization parameters are set as follows: first-stage depressurization: 1.0 MPa, second-stage depressurization: 0.4 MPa, and third-stage depressurization: 0.1 MPa.

[0062] Example 2

[0063] The composition and preparation process are the same as in Example 1, except that: In the preparation process, the S12 is added in parallel flow at a temperature of 60°C, washed with deionized water at 60°C, calcined at 500°C for 4 hours, and the other steps are the same.

[0064] In the preparation process S13, the mass percentage of the adhesive solvent dilute nitric acid is 2wt%, the extrusion aid guar gum powder is 2wt%, the lubricant graphite is 1wt%, and the other components are the same.

[0065] The drying process in step S22 of the preparation process is set with the following parameters: temperature 100℃, duration 6h, and holding time of 3h during programmed temperature rise vulcanization. Other steps are the same.

[0066] The multifunctional composite adsorbent in the S22 preparation process has the following composition of raw materials by mass percentage: 10% tetrabutyl titanate, 15% ammonium metatungstate, 3% copper acetate, and the balance being aluminum nitrate, with other components being the same.

[0067] In process S31, the volume ratio of hydrogen to waste lubricating oil is 300:1, and the other components are the same.

[0068] In the preparation process S32, the mass ratio of the oxygen-containing solvent methanol to the oil-hydrogen mixture is 0.08:1, and the other components are the same.

[0069] In step S33 of the preparation process, the pressure reduction is set as follows: first-stage pressure reduction: 0.8 MPa, second-stage pressure reduction: 0.3 MPa, third-stage pressure reduction: 0.05 MPa, and other steps are the same.

[0070] Example 3

[0071] The composition and preparation process are the same as in Example 1, except that: In the preparation process, the co-current droplet addition temperature in S12 is 80℃, the washing is done with 80℃ deionized water, the calcination temperature is 600℃, the holding time is 6h, and other steps are the same.

[0072] In the preparation process S13, the mass percentage of the adhesive solvent dilute nitric acid is 6 wt%, the extrusion aid guar gum powder is 5 wt%, the lubricant graphite is 3 wt%, and the other components are the same.

[0073] The drying process in step S22 of the preparation process is set with the following parameters: temperature 120℃, duration 8h, temperature holding time in the programmed temperature rise vulcanization is 5h, and other steps are the same.

[0074] The multifunctional composite adsorbent in the S22 preparation process has the following composition of raw materials by mass percentage: 30% tetrabutyl titanate, 25% ammonium metatungstate, 8% copper acetate, and the balance being aluminum nitrate. Other components are the same.

[0075] In process S31, the volume ratio of hydrogen to waste lubricating oil is 500:1, and the other components are the same.

[0076] In the preparation process S32, the mass ratio of the oxygen-containing solvent methanol to the oil-hydrogen mixture is 0.15:1, and the other components are the same.

[0077] In step S33 of the preparation process, the pressure reduction is set as follows: first-stage pressure reduction: 1.2 MPa, second-stage pressure reduction: 0.5 MPa, third-stage pressure reduction: 0.15 MPa, and other steps are the same.

[0078] Example 4

[0079] The composition and preparation process are the same as in Example 1, except that: In the preparation process, the co-current droplet addition temperature in S12 is 65℃, the washing is done with 65℃ deionized water, the calcination temperature is 580℃, the holding time is 4.5h, and other steps are the same.

[0080] In the preparation process S13, the mass percentage of the adhesive solvent dilute nitric acid is 5 wt%, the extrusion aid guar gum powder is 4 wt%, the lubricant graphite is 2.5 wt%, and the other components are the same.

[0081] The drying process in step S22 of the preparation process is set with the following parameters: temperature 105℃, duration 6.5h, and holding time in the programmed temperature rise vulcanization is 4.5h. Other steps are the same.

[0082] The multifunctional composite adsorbent in the S22 preparation process has the following composition of raw materials by mass percentage: butyl titanate 24%, ammonium metatungstate 16%, copper acetate 7%, and the balance being aluminum nitrate, with other components being the same.

[0083] In process S31, the volume ratio of hydrogen to waste lubricating oil is 450:1, and the other components are the same.

[0084] In the preparation process S32, the mass ratio of the oxygen-containing solvent methanol to the oil-hydrogen mixture is 0.09:1, and the other components are the same.

[0085] In step S33 of the preparation process, the pressure reduction is set as follows: first-stage pressure reduction: 0.9 MPa, second-stage pressure reduction: 0.5 MPa, third-stage pressure reduction: 0.13 MPa, and other steps are the same.

[0086] Comparative Example 1 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, the active component loading is removed, and only a simple alumina carrier is used to fill the fixed bed. The other steps are the same.

[0087] Comparative Example 2 The composition and preparation process are the same as in Example 1, except that: In step S3 of the preparation process, the entry of oxygen-containing solvents is removed, there is no backflow of oxygen-containing solvents, and only an oil-hydrogen mixture is used. The other steps are the same.

[0088] Comparative Example 3 The composition and preparation process are the same as in Example 1, except that: In step S3 of the preparation process, the composite adsorbent of the present invention is removed and replaced with a Mo-Ni catalyst, while the other steps remain the same.

[0089] Based on Examples 1-4 and Comparative Examples 1-3, samples of the final purified oil and waste mineral oil were taken for organochlorine removal rate testing: the high-temperature combustion microcoulometric method was used, referring to the standard GB / T 18612-2011 "Determination of Organochlorine Content in Crude Oil".

[0090] Based on Examples 1-4 and Comparative Examples 1-3, samples of the final purified oil and waste mineral oil were taken for gum removal rate testing, referring to standard GB / T 8926-2012 "Determination of Insoluble Matter in Lubricating Oils in Use".

[0091] Based on Examples 1-4 and Comparative Examples 1-3, samples of the final purified oil and untreated waste mineral oil were taken and tested for metal removal rate and organosilicon removal rate, referring to the standard GB / T 10476-2023 "Determination of Multiple Elements in Lubricating Oils and Base Oils by Inductively Coupled Plasma Atomic Emission Spectrometry".

[0092] The specific test results are shown in Table 2. Figure 3 , Figure 4 As shown: Table 2 Comparison of core performance of Examples 1-4 and Comparative Examples 1-3 ;

[0093] The comparison results above show that Example 1 has the best overall performance and achieves the goal of "deep removal". This is due to the optimized composite carrier preparation parameters forming the most suitable pore structure and acidic sites, the optimal active component ratio providing the strongest adsorption and reaction activity, and the most coordinated process conditions, achieving perfect synergy between extraction and adsorption. The overall performance of Examples 2 to 4 is slightly lower than that of Example 1, but still maintains a high level, indicating that excellent removal effect was still achieved under a large range of parameter variations. The removal rate of organochlorine and silicon in Comparative Example 1 is extremely low, which proves that the alumina carrier alone does not have the ability to selectively adsorb and convert organochlorine and silicon. Its limited degumming and metal removal capabilities mainly rely on physical adsorption and filtration. Although the composite adsorbent in Comparative Example 2 has certain capabilities, it lacks the synergistic effect of countercurrent extraction with methanol solvent, resulting in a significant reduction in efficiency. Comparative Example 3 uses conventional hydrogenation catalysis, and its selective adsorption and scale-holding capabilities are far lower than those of the composite adsorbent. Chlorine and silicon will irreversibly poison its acidic and metal sites, leading to rapid deactivation and failure to deeply remove impurities.

[0094] In summary, as can be clearly seen from the above embodiments and comparative examples, the waste mineral oil suspension bed hydrocatalytic treatment process provided by the present invention is significantly superior to traditional methods in terms of desiliconization, dechlorination, removal of colloids and metals. This is attributed to the technical route that combines a novel multifunctional composite adsorbent with a multi-stage countercurrent extraction-adsorption coupling process. This approach maximizes the removal of chlorine and silicon impurities before the hydrogenation reaction, avoiding catalyst poisoning and equipment corrosion. Furthermore, it also removes harmful components such as colloids and metals from the waste oil to a certain extent, thereby significantly extending the operating cycle of the hydrogenation unit and improving the quality of the product oil.

Claims

1. A waste mineral oil suspension bed hydrocatalytic treatment process, characterized in that: The waste mineral oil suspension bed hydrocatalytic treatment process utilizes a multifunctional composite adsorbent and a multi-stage countercurrent extraction-adsorption coupling process. The multifunctional composite adsorbent, through a modified alumina-titanium oxide composite carrier, enhances its capacity to accommodate and adsorb large molecular impurities and polar compounds. Tungsten is used as the main active component to promote the hydrodechlorination reaction of organochlorides. Copper acts as an auxiliary agent to regulate the dispersion and valence state of tungsten, and its sulfides react with HCl generated during hydrodechlorination to form stable metal chlorides, thereby fixing chlorine on the adsorbent and preventing damage to downstream equipment. The multi-stage countercurrent extraction-adsorption coupling process leverages the polar selectivity of oxygen-containing solvents to extract and dissolve some polar chlorine- and silicon-containing compounds from the waste mineral oil into the solvent phase, promoting alcoholysis of silicon-oxygen bonds to reduce the adsorbent load. The multi-stage, segmented packing of the composite adsorbent within the tower performs stepwise adsorption and catalytic conversion of residual chlorine and silicon impurities that were not extracted.

2. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 1, characterized in that: The multifunctional composite adsorbent has the following composition of raw materials in the following mass percentages: butyl titanate 10-30%, ammonium metatungstate 15-25%, copper acetate 3-8%, and the balance being aluminum nitrate.

3. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 1, characterized in that: The multi-stage countercurrent extraction-adsorption coupling process adopts a countercurrent flow of oil from bottom to top and oxygen-containing solvent from top to bottom, so that each stage can exert its extraction and adsorption efficiency, ultimately achieving deep removal of impurities.

4. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 1, characterized in that: The modified alumina-titanium oxide composite carrier comprises a peptide dilute nitric acid, an extrusion aid guar gum powder, and a lubricant graphite, wherein the peptide dilute nitric acid accounts for 2-6 wt%, the extrusion aid guar gum powder accounts for 2-5 wt%, and the lubricant graphite accounts for 1-3 wt%.

5. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 1, characterized in that, The purified oil obtained after treatment with the multifunctional composite adsorbent and the multi-stage countercurrent extraction-adsorption coupling process has an organochlorine removal rate of over 95% and an organosilicon removal rate of over 95%.

6. The waste mineral oil suspension bed hydrocatalytic treatment process according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Preparation of the composite carrier; S11: Dissolve aluminum nitrate in deionized water and tetrabutyl titanate in anhydrous ethanol, then mix the two under stirring to form a salt solution mixture; S12: The salt solution mixture prepared in S11 is added dropwise in parallel with the precipitant ammonia water. After the addition is complete, the mixture is stirred, aged, washed, and dried to finally obtain a dry powder. S13: The dry powder prepared in S12 is mixed with the adhesive solvent dilute nitric acid, the extrusion aid guar gum powder, and the lubricant graphite, then extruded into strips by an extruder, and finally calcined to obtain the modified alumina-titanium oxide composite carrier. S2: Active component loading; S21: Dissolve ammonium metatungstate and copper acetate together in deionized water and stir to obtain an impregnation solution; S22: The impregnation solution prepared in S21 is used to impregnate the modified alumina-titanium oxide composite carrier prepared in S13 with an equal volume, and then aged, dried, sulfided by programmed temperature rise, and passivated to obtain a multifunctional composite adsorbent. S3: Multi-stage countercurrent extraction-adsorption coupling process; S31: Waste mineral oil is filtered and dehydrated to remove mechanical impurities, solid particles, free water and emulsified water; then it is pressurized and mixed with hydrogen to obtain an oil-hydrogen mixture. S32: The oil-hydrogen mixture prepared by S31 enters from the bottom of the adsorption tower, and the oxygen-containing solvent methanol enters from the top after being pressurized. The oil phase passes through a fixed bed containing a multifunctional composite adsorbent prepared by S22 to obtain purified oil. S33: The purified oil prepared in S32 is cooled and then subjected to gas-liquid separation under high pressure. The liquid phase is depressurized to remove dissolved trace amounts of solvent and light hydrocarbons, resulting in the final purified oil product.

7. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 6, characterized in that: The parameters for the co-current dripping described in S12 are: temperature 60-80℃, pH 9; The washing described in S12 involves washing with deionized water at 60-80°C until no chloride ions are precipitated in the filtrate when tested with silver nitrate solution. The drying process described in S12 has the following parameters: temperature 120℃, duration 12h. The roasting parameters described in S13 are as follows: heating rate 3℃ / min, temperature 500~600℃, and holding time 4~6h.

8. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 6, characterized in that: The drying process described in S22 has the following parameters: temperature 100-120℃, duration 6-8h. The programmed temperature rise vulcanization described in S22 has the following parameter settings: first, an inert gas is introduced to purge air, then a sulfur-containing atmosphere is introduced; in the low-temperature stage, the temperature is raised from room temperature to 150°C at a rate of 1°C / min; in the medium-temperature stage, the temperature is raised from 150°C to 250°C at a rate of 2°C / min; in the high-temperature stage, the temperature is raised from 250°C to 380°C at a rate of 1°C / min, and the holding time is 3–5 hours; the sulfur-containing atmosphere is H2 containing 10% H2S. The passivation described in S22 is performed using an inert gas N2 containing 1% O2 at room temperature.

9. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 6, characterized in that: The pressure boosting described in S31 has the following parameter settings: pressure is 4.0 MPa; The hydrogen gas described in S31 has a volume ratio of 300:1 to 500:1 with the waste lubricating oil. The oxygen-containing solvent methanol described in S32 has a mass ratio of 0.08:1 to 0.15:1 with the oil-hydrogen mixture.

10. The waste mineral oil suspension bed hydrocatalytic treatment process according to claim 6, characterized in that: The high pressure described in S33 has the following parameter settings: pressure 4.0 MPa, temperature 50℃; The pressure reduction described in S33 has the following parameter settings: first-stage pressure reduction: 0.8-1.2 MPa, second-stage pressure reduction: 0.3-0.5 MPa, and third-stage pressure reduction: 0.05-0.15 MPa.

Citation Information

Patent Citations

  • Method and system for recycling waste mineral oil residues

    CN112625723A

  • Dehydration and purification process for waste mineral oil

    CN116103061A

  • Process for regenerating base oil from waste lubricating oil

    CN119264973A

  • Method for processing waste oil and / or oil / water mixtures or similar fluid mixtures

    EP1947165A1

  • catalyst, METHOD FOR PREPARING SUPPORT, METHOD FOR PREPARING CATALYST AND METHOD FOR HYDROCARBON FEEDSTOCK HYDRO-PURIFICATION

    RU2015151071A

Cited By

  • Separation method and separation device for organic silicon in waste oil

    CN121988074A